A paradoxical switch: the implications of excitatory GABAergic signaling in neurological disorders - McArdle, Colin J.; Arnone, Alana A.; Heaney, Chelcie F.; Raab-Graham, Kimberly F. (Frontiers in Psychiatry, 2024)
Gamma-aminobutyric acid (GABA) is the primary inhibitory neurotransmitter in the central nervous system. In the mature brain, inhibitory GABAergic signaling is critical in maintaining neuronal homeostasis and vital human behaviors such as cognition, emotion, and motivation. While classically known to inhibit neuronal function under physiological conditions, previous research indicates a paradoxical switch from inhibitory to excitatory GABAergic signaling that is implicated in several neurological disorders. Various mechanisms have been proposed to contribute to the excitatory switch such as chloride ion dyshomeostasis, alterations in inhibitory receptor expression, and modifications in GABAergic synaptic plasticity. Of note, the hypothesized mechanisms underlying excitatory GABAergic signaling are highlighted in a number of neurodevelopmental, substance use, stress, and neurodegenerative disorders. Herein, we present an updated review discussing the presence of excitatory GABAergic signaling in various neurological disorders, and their potential contributions towards disease pathology.